Effectiveness of social egg freezing: protocol for systematic review and meta-analyses - Zhuoyang Li; Elizabeth Sullivan; Alex Wang; Fekede Asefa Kumsa; Iain Kaan; Cynthia M Farquhar (BMJ Open)
Introduction Social egg freezing is storing egg for the purpose of preserving fertility and delayed childbearing. Currently, little is known about the utilisation and effectiveness of this approach. This review aims to determine (1) the proportion of women who used their stored eggs, and (2) the egg survival rate through vitrification, and the clinical pregnancy rate and live birth rate per 100 women partaking in the procedure, and among women who stored their eggs for medical reasons.Methods and analyses This systematic review will be done according to the items listed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. PubMed, Embase, Scopus, The Cumulative Index to Nursing and Allied Health Literature (CINAHL) and the Cochrane Library and Health Technology Assessment databases will be searched to identify eligible studies published since 2012. Two reviewers will independently appraise the eligibility and quality of the studies based on preset checklists and extract the data using a data extraction template. Outcomes of interest are proportion of women who used their stored eggs, egg survival rate, pregnancy rate and live birth rates. We will determine the presence heterogeneity among studies using the Cochrane’s Q test. The percentage of total variation across studies, which is due to statistical heterogeneity, will be calculated using the I2 statistics. Outcomes of interest will be pooled together using metaprop programme STATA V.14.Ethics and dissemination For this review, ethical committee approval is not required. We will use publically available data from previously published studies. The final report of the review will be disseminated through publication on national or international journal, and it will be presented on different scientific conferences.PROSPERO registration number CRD42018114254.